Seismic assessment of a heavy-timber frame structure with ring-doweled moment-resisting connections - Rodrigues, Leonardo G.; Branco, Jorge M.; Neves, Luís C.; Barbosa, André R. (Springer Verlag, 2017)
The performance of heavy-timber structures in earthquakes depends strongly on the inelastic behavior of the mechanical connections. Nevertheless, the nonlinear behavior of timber structures is only considered in the design phase indirectly through the use of an R-factor or a q-factor, which reduces the seismic elastic response spectrum. To improve the estimation of this, the seismic performance of a three-story building designed with ring-doweled moment resisting connections is analyzed here. Connections and members were designed to fulfill the seismic detailing requirements present in Eurocode 5 and Eurocode 8 for high ductility class structures. The performance of the structure is evaluated through a probabilistic approach, which accounts for uncertainties in mechanical properties of members and connections. Nonlinear static analyses and multi-record incremental dynamic analyses were performed to characterize the q-factor and develop fragility curves for different damage levels. The results indicate that the detailing requirements of Eurocode 5 and Eurocode 8 are sufficient to achieve the required performance, even though they also indicate that these requirements may be optimized to achieve more cost-effective connections and members. From the obtained fragility curves, it was verified that neglecting modeling uncertainties may lead to overestimation of the collapse capacity.